Investigating hydrogenation and decarbonylation in vapor-phase furfural hydrotreating over Ni/SiO2 catalysts: Propylene production - Chen, Szu-Hua; Tseng, Ya-Chun; Yang, Sheng-Chiang; Lin, Shawn D. (Applied catalysis. A, General, 2021)
[Display omitted] •A full furfural utilization, either to furfuryl alcohol (a biofuel) or to propylene and furan (as chemical feedstock), can be realized with proper design of Ni-catalyst and operation of reaction.•This design can be related to Ni structure sensitive, the terrace sites prefer the hydrogenation as furfuryl alcohol production, and the step/edge sites prefer the decarbonylation as propylene production, together with proper operation.•This disclosed approach will be applied to sustainable bio-refinery processes and scientific fields over non-expensive Ni catalysts. Furfural can be mass-produced from lignocellulose biomass and can be a platform chemical for producing valuable chemicals. In this study, we examine Ni/SiO2 catalysts for the conversion of furfural under a hydrogen atmosphere. The reactivity and the product selectivity are governed by the reaction temperature and the Ni particle size. A catalyst pretreatment by including calcination prior to hydrogen reduction leads to Ni/SiO2–CR with large Ni particles (∼ 15 nm) and a high selectivity to furfuryl alcohol (FA) at below 200 °C. The Ni/SiO2-R is hydrogen-pretreated without a prior calcination and it contains small Ni particles (∼ 5 nm) and exhibits relatively high selectivity to furan. The turnover frequency (TOF) of furfural conversion is 239 and 408 h−1, respectively, on Ni/SiO2-CR and Ni/SiO2-R at 175 °C, when the former shows 100% selectivity to FA and the latter exhibits a selectivity of around 38% and 62%, to FA and furan, respectively. Moreover, the furan can be reacted to produce propylene and CO by the Ni catalysts at above 200 °C and Ni/SiO2-R exhibits a higher activity than Ni/SiO2-CR. The results suggest that the furfural hydrotreating reaction over Ni catalysts is structure sensitive and a proper design of catalyst and operating temperature can provide a full furfural utilization, either to FA (a biofuel), or to furan and propylene (as chemical feedstock).